Survei Sarana dan Prasarana Pendidikan Jasmani Sekolah Dasar di Kecamatan Mertoyudan Kabupaten Magelang - Sulistiyono, Mei Sulistiyono; Qoriah, Anirotul (Universitas Negeri Semarang, 2023)
The purpose of the study was to determine the state and condition of the physical education learning facilities and insfrastructure for Elementary Schools in Mertoyudan District,Magelang Regency. This research method is a survey with a quantitative descriptive approach. The location if this research is in Magelang Regency with a target of 10 Elementary schools in Mertoyudan District, Magelang Regency. Data collection techniques using qouta sampling technique, the instruments used are observation, documentation and interviews with the Principal and Physical Education Teachers. The results of this study indicate that the condition and existence of Elementary School Physical Education Facilities in Mertoyudan District, Magelang Regency are in the good category (40%), sufficient category (60%),and less category (0%). meanwhile, the result of the insfrastructure condition are in goos category (10%), sufficient category (80%), and poor category (1%). The conclusion of this study is that the existing facilities and infrastructure in the Mertoyudan District Elementary school are in the sufficient category. suggestions from this research are that the agency at the school can help manage and maintain the facilities and infrastructure they have and modity the existing facilities and infrastructure in the school, especially in elementary schools for the Mertoyudan District, Magelang Regency.